“Prompt, at any time of the day…”: the Emerging Translatorial Habitus in the Late Habsburg Monarchy - Wolf, Michaela (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2013)
As one of the key notions in French sociology, habitus has also lately conquered the field of translation studies, at least from the perspective of a sociologically-oriented view of translation. In this paper I will critically highlight the main factors responsible for the term’s potential for translation purposes. Within the discussion of its adoption in translation studies, I will test the enduring claim of the translator’s submissiveness allegedly related to the translatorial habitus. On the basis of a case study on the private (commercial) translation sector in the late Habsburg Monarchy, I will focus on three aspects to substantiate my assumption that towards the end of the nineteenth century, the commercial translators’ activity was already characterized by explicit emancipating processes, mostly driven by the struggle for recognition in the field: the initially weak structure of the field; the habitus as a product of the relation between its collective and individual history; the conditions triggering the dynamism of the translator’s habitus. I will attempt to develop a differentiated view on the habitus concept, challenging traditional discussions of its informative value.